The Effect of Product Innovation, Brand Awareness and Price Perception on Repurchase Decisions Through Customer Satisfaction with Social Media Marketing Activity & Perceived Value as Moderating Variables on Sagiko Float Fruit Juice Drink in the Kediri Residency Area East Java - Viando, Feterrido Wahyu; Cempena, Ida Bagus; Endah Budiarti (International Journal of Economics (IJEC), 2025)
The food and beverage (F&B) industry in Indonesia is currently experiencing rapid growth. Changes in lifestyle, especially in big cities where people like fast food and drinks, coupled with the active use of digital platforms, have a transformational impact on digitalization and open up opportunities for F&B business actors to promote their products to Internet users. This study aims to find empirical evidence regarding the effect of product innovation, brand awareness, and price perception on repurchase decisions through customer satisfaction, with social media marketing activity and perceived value as moderating variables on Sagiko float fruit juice drinks in the Kediri residency area east Java. The population in this study was customers who had made purchases at the Sagiko float in the Kediri residency area east Java. The sampling technique used was purposive sampling, which was to randomly select customers who had made purchases at Sagiko Float in the Kediri residency area east Java, with a total of 300 respondents. Hypothesis testing was conducted using the Structural Equation Modeling (SEM) approach or structural equation model with the Analysis of Moment Structures (AMOS)  version 26 program. Based on the results of the analysis of the seven tested hypotheses, all were proven to be accepted, namely that product innovation, brand awareness, price perception, social media activity, and perceived value have a significant effect on repurchase decisions and customer satisfaction. This study provides insights for companies in designing effective marketing strategies to increase customer satisfaction and the intensity of consumen repurchase decisions by increasing product innovation, brand awareness, price perception, and marketing activities on social media and perceived value